Mobile-web food recommendation system based on food reviews - Guo, Fuqiang (Nanyang Technological University, 2021)
In this project, we aim to develop a recommendation system for food items in NTU canteens and restaurants. In the system, a user can select a particular canteen, stall or restaurant and the system will display a list of recommended food items according to user reviews or ratings. To build the system, the student will need to gather a database of restaurants in NTU with pictures on their food items, if available. The review results will be gathered from users using the system. In addition, we also develop a mobile client for the system. The mobile client will be developed based on Android hand phones, and the mobile app should be connected a web server.